Catalytic Neutralization of Water Pollutants Mediated by Dendritic Polymers - Michael Arkas; Ioannis Anastopoulos; Dimitrios A. Giannakoudakis; Ioannis Pashalidis; Theodora Katsika; Eleni Nikoli; Rafael Panagiotopoulos; Anna Fotopoulou; Michail Vardavoulias; Marilina Douloudi (Nanomaterials, 2022)
Radially polymerized dendritic compounds are nowadays an established polymer category next to their linear, branched, and cross-linked counterparts. Their uncommon tree-like architecture is characterized by adjustable internal cavities and external groups. They are therefore exceptional absorbents and this attainment of high concentrations in their interior renders them ideal reaction media. In this framework, they are applied in many environmentally benign implementations. One of the most important among them is water purification through pollutant decomposition. Simple and composite catalysts and photo-catalysts containing dendritic polymers and applied in water remediation will be discussed jointly with some unconventional solutions and prospects.